Relação entre transtorno do ciclo vigília-sono e trabalho noturno: desafios à segurança e saúde do trabalhador - Benites, Andréa Carolina [UNESP]; Camargo, Iara Sigaud; Goulart Júnior, Edward [UNESP]; Camargo, Mário Lázaro [UNESP] (My University, 2013)
The work and work organization influence the evolution of the health-disorder process by establishing a causal link with the work and the disorder. The present study aimed to verify the presence of the disorder of the sleepwake cycle triggered by non-organic factors, by identifying the possible effects on physical health, mental health and the social and family relations ten watchmen of a public institution of higher education. It was found that 80% of respondents had one or more of the symptoms that meet the criteria for the diagnosis of this non-organic disorder of sleep-wake cycle. We emphasize the need for specialized diagnostic, medical, psychological and social support for this population

O trabalho e a organização laboral influenciam a evolução do processo saúde-doença estabelecendo um nexo causal da doença com o trabalho. O presente estudo teve por objetivo verificar a presença do transtorno do ciclo vigília-sono devido a fatores não orgânicos, identificando possíveis efeitos na saúde física, mental, no social e nas relações familiares de dez vigias noturnos de uma instituição pública de ensino superior. Verificou-se que 80% dos entrevistados apresentaram um ou mais dos sintomas que correspondem aos critérios para o diagnóstico. Salienta-se a necessidade de diagnóstico especializado, acompanhamento médico, psicológico e social para esta população.
Relationship between disorder sleep-wake cycle and night work: challenges to the safety and health of workers
Keywords: Sleep disorders; Night work; Worker health; Transtornos do sono; Trabalho noturno; Saúde do trabalhador